Impact of Sales, Net Profit, and EPS on Stock Behavior in Emerging Markets : A Study of Indian Companies - Sharma, Gagan Deep; Mahendru, Mandeep; Singh, Sanjeet (Indian Journal of Research in Capital Markets, 2015)
The present study investigated the effects of sales, net profit, and earnings per share on the stock behavior of NSE-listed companies. Thirty five major companies were chosen from the companies listed at NSE. The study is based on quarterly data of sales, net profit, and EPS from the period of 2001 to 2010. Descriptive statistics, correlation, regression, unit-root test, and Granger’s causality were used for data analysis. The study found no visible effect of sales, earnings per share, and net profit on the future stock prices. These results indicated that no abnormal profits could be made by trading in the stocks on the basis of sales, earnings per share, and net profit.